2022
DOI: 10.1002/jrsm.1602
|View full text |Cite
|
Sign up to set email alerts
|

End‐user understanding of qualitative comparative analysis used within evidence synthesis: A mixed‐methods study

Abstract: Background: Enhanced uptake of systematic reviews that use qualitative comparative analyses (QCA) requires knowing how end-users interpret such findings. The study purpose was to identify effective approaches to communicating results from a QCA within a systematic review. Methods: Sequential exploratory mixed methods design; thematic analysis of interviews with 11 end-users followed by a randomized experiment with 254 participants that provided QCA results for a hypothetical review presented through three form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
2
0
0
Order By: Relevance
“…Our project’s findings recommend evidence synthesis summaries which minimise methodological details. This is also supported by previous research with end-users of systematic reviews [ 21 ] which found that unfamiliar methods and terminology were barriers to fully understanding findings. A brief mention of methods, emphasizing key messages, and avoiding GRADE terminology (i.e., ‘low-certainty evidence’) is also promoted by Cochrane’s guidance for plain language summaries (PLS) [ 22 ].…”
Section: Discussionsupporting
confidence: 81%
“…Our project’s findings recommend evidence synthesis summaries which minimise methodological details. This is also supported by previous research with end-users of systematic reviews [ 21 ] which found that unfamiliar methods and terminology were barriers to fully understanding findings. A brief mention of methods, emphasizing key messages, and avoiding GRADE terminology (i.e., ‘low-certainty evidence’) is also promoted by Cochrane’s guidance for plain language summaries (PLS) [ 22 ].…”
Section: Discussionsupporting
confidence: 81%
“…(4) Our project's ndings recommend evidence synthesis summaries which minimise methodological details. This is also supported by previous research with endusers of systematic reviews (20) which found that unfamiliar methods and terminology were barriers to fully understanding ndings. A brief mention of methods, emphasizing key messages, and avoiding GRADE terminology (i.e., 'low-certainty evidence') are also promoted by Cochrane's guidance for plain language summaries (PLS).…”
Section: Discussionsupporting
confidence: 76%